Managers' gender role attitudes: a country institutional profile approach - Parboteeah, K Praveen; Hoegl, Martin; Cullen, John B (Journal of International Business Studies, 2008)
In this paper, we use the country institutional profile to investigate how selected cognitive, normative, and regulative aspects of various countries relate to traditional gender role attitudes of managers from these countries. Our cross-level analyses, using hierarchical linear modeling, control for a number of individual characteristics (i.e., age, education, gender, and social class). Results support our hypotheses that managers' traditional gender role attitudes relate positively to nation-level uncertainty avoidance and power distance. Moreover, the results support our predictions that gender egalitarian normative institutions, degree of regulation, and degree of educational development are negatively related to managers' traditional gender role attitudes. However, results reject our hypotheses regarding nation-level religiosity, assertiveness, and masculinity, not showing the proposed relationship with managers' traditional gender role attitudes. Implications for research and practice are discussed.